An Oresteia - Aeschylus v525-v456; Sophocles ca. 497/496 v. Chr.-406 v. Chr; Euripides ca. 485/480 v. Chr.-406 v.Chr (Faber & Faber, 2010)
In this innovative rendition of The Oresteia, the poet, translator, and essayist Anne Carson combines three different visions -- Aischylos' Agamemnon, Sophokles' Elektra, and Euripides' Orestes, giving birth to a wholly new experience of the classic Greek triumvirate of vengeance. Carson's accomplished rendering combines elements of contemporary vernacular with the traditional structures and rhetoric of Greek tragedy, opening up the plays to a modern audience. --from publisher description